Analisis Kepuasan Pelanggan dalam Memilih Minimarket di Kecamatan Sipora Utara - Supriyanti Neneng, Ides; Zega, Asokhiwa (CV. SINAR HOWUHOWU, 2024)
This study aims to analyze the factors that influence customer satisfaction in choosing a minimarket in North Sipara District. Customer satisfaction is an important element in maintaining competitive advantage, especially in the highly competitive retail sector. This research uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 200 respondents who are minimarket customers in the region. The variables analyzed include service quality, price, convenience, and product availability. Data analysis was carried out using multiple linear regression techniques to determine the effect of each variable on customer satisfaction. The results showed that service quality and convenience have a significant influence on customer satisfaction. Meanwhile, price and product availability have a lower influence than the other two variables. The discussion of these results indicates that customers value a comfortable shopping experience and good service more than price. Based on these findings, it is recommended that minimarket managers in North Sipara Sub-district focus more on improving service quality and improving facilities that support customer convenience. The conclusion is that customer satisfaction is not only determined by price and product availability, but also by the overall shopping experience. The findings provide practical implications for minimarket management in the area, namely the importance of service strategies that focus on convenience and quality. Thus, this study contributes to the development of retail management, particularly in the context of minimarkets in developing rural areas.